Ultraviolet-C radiation and atmospheric pressure plasma jet treatment as sanitation agents against Listeria monocytogenes on stainless steel surfaces - Valerio, Myca Ann D. (College of Home Economics, University of the Philippines Diliman, 2016)
This study aimed to establish the efficacy of ultraviolet-C irradiation (UV-C) and atmospheric pressure plasma jet on the inactivation of Listeria monocytogenes on two types of stainless steel, 304 and 316, with three different surface finishes each namely 2B, hairline (HL), and mirror (MR). The mid-stationary growth phase of two strains of Listeria monocytogenes was identified and established at 17 h, and it was used as the enrichment time for the cocktail of microorganisms prior to use for surface adhesion. A cocktail of L. monocytogenes was allowed to attach on test surfaces for 4 h and it was subjected to UV-C irradiation and atmospheric pressure plasma jet treatment. Results obtained from the UV-C treatment showed biphasic inactivation behavior with D1-values and maximum log reduction that ranged from 1.56 (316 MR) to 2.90 s (304 2B) and 0.66 (316 2B) to 0.74 log CFU/cm2 (316 MR), respectively. On he other hand, the atmospheric pressure plasma jet showed results with logarithmic linear death curves with Dvalues that ranged from 1.66 (316 2B) to 2.22 s (316 MR). The efficacies of the two sanitizing agents showed no significant relationship with the different types of stainless steel and surface finishes. The results obtained imply that UV-C can be coupled with chemical sanitizing agents to address its limitations, while atmospheric pressure plasma jet can be utilized solely for food contact surfaces.